2019
DOI: 10.3390/pharmaceutics11070352
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Antibiotics for Mycobacterial Lung Disease

Abstract: Mycobacterial lung diseases are an increasing global health concern. Tuberculosis and nontuberculous mycobacteria differ in disease severity, epidemiology, and treatment strategies, but there are also a number of similarities. Pathophysiology and disease progression appear to be relatively similar between these two clinical diagnoses, and as a result these difficult to treat pulmonary infections often require similarly extensive treatment durations of multiple systemic drugs. In an effort to improve treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 151 publications
(181 reference statements)
0
17
0
1
Order By: Relevance
“…Liposomal ciprofloxacin is prepared using negatively charged liposomes (liposome surfaces coated with polyethylene glycol or PEG) and is delivered by inhalation or intravenous routes. In preclinical studies liposomal ciprofloxacin has shown great promise in the treatment of P. aeruginosa and MAC lung infections, since it was able to infiltrate established biofilms and penetrate infected macrophages [56][57][58]. The in vivo release profile after intratracheal instillation in mice confirmed that the liposomal formulation satisfied the requirement for sustained levels of ciprofloxacin in the lung for a duration of 24 h, having a lung clearance half-life after inhalation of approximately 12 h (compared with 1 h for free ciprofloxacin).…”
Section: Liposomal Ciprofloxacin For Inhalationmentioning
confidence: 99%
“…Liposomal ciprofloxacin is prepared using negatively charged liposomes (liposome surfaces coated with polyethylene glycol or PEG) and is delivered by inhalation or intravenous routes. In preclinical studies liposomal ciprofloxacin has shown great promise in the treatment of P. aeruginosa and MAC lung infections, since it was able to infiltrate established biofilms and penetrate infected macrophages [56][57][58]. The in vivo release profile after intratracheal instillation in mice confirmed that the liposomal formulation satisfied the requirement for sustained levels of ciprofloxacin in the lung for a duration of 24 h, having a lung clearance half-life after inhalation of approximately 12 h (compared with 1 h for free ciprofloxacin).…”
Section: Liposomal Ciprofloxacin For Inhalationmentioning
confidence: 99%
“…Non-tuberculous mycobacteria, primarily caused by Mycobacterium avium complex and Mycobacterium abscessus, lung infections are found in immunocompromised and otherwise functionally compromised lungs. It is particularly serious in cystic fibrosis patients and a portion of the elderly population identified in Lady Windermere Syndrome [47][48][49]. The disease manifests as extracellular biofilms associated with bronchiectasis and intracellular disease in lung macrophages [50].…”
Section: Diseases Therapymentioning
confidence: 99%
“…5 This process leads to an immune response that results in granuloma formation, a phenomenon that allows NTM strains to survive. 5,13 The consequences of tuberculosis infections (M. tuberculosis) are typically more severe and are characterized by cavitary lung disease that leads to increased mortality. It is important to note, however, that lung cavity formation is present in some rare cases of NTM infection.…”
Section: Mechanism Of Infection and Epidemiologymentioning
confidence: 99%
“…It is important to note, however, that lung cavity formation is present in some rare cases of NTM infection. 5 The symptoms of NTMinduced pulmonary disease are variable, but nearly all patients present with a chronic or recurring cough. 29 Variable symptoms include fever, fatigue, increased sputum production, hemoptysis, dyspnea, chest pain, and weight loss.…”
Section: Mechanism Of Infection and Epidemiologymentioning
confidence: 99%